2016
DOI: 10.1534/g3.116.028324
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 Limits DNA Methylation in Neurospora crassa

Abstract: Histone H1 variants, known as linker histones, are essential chromatin components in higher eukaryotes, yet compared to the core histones relatively little is known about their in vivo functions. The filamentous fungus Neurospora crassa encodes a single H1 protein that is not essential for viability. To investigate the role of N. crassa H1, we constructed a functional FLAG-tagged H1 fusion protein and performed genomic and molecular analyses. Cell fractionation experiments showed that H1-3XFLAG is a chromatin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 78 publications
4
11
0
Order By: Relevance
“…Similar to both S. cerevisiae and S. pombe cells, we were readily able to isolate nucleosome footprints from N. crassa using the rapid MNase protocol ( Figure 3D). Importantly, we verified that the genomic nucleosome positions that we obtained were similar to previously-published N. crassa data sets (SEYMOUR et al 2016;KLOCKO et al 2019) ( Figure 3E). Together these data validate the rapid MNase protocol as a reasonable, rapid strategy to map nucleosome positions in S. pombe and N. crassa, two widely-investigated model fungi.…”
Section: Rapid Recovery Of Nucleosome Footprints From S Pombe and Nsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to both S. cerevisiae and S. pombe cells, we were readily able to isolate nucleosome footprints from N. crassa using the rapid MNase protocol ( Figure 3D). Importantly, we verified that the genomic nucleosome positions that we obtained were similar to previously-published N. crassa data sets (SEYMOUR et al 2016;KLOCKO et al 2019) ( Figure 3E). Together these data validate the rapid MNase protocol as a reasonable, rapid strategy to map nucleosome positions in S. pombe and N. crassa, two widely-investigated model fungi.…”
Section: Rapid Recovery Of Nucleosome Footprints From S Pombe and Nsupporting
confidence: 87%
“…pombe (THODBERG et al 2019). Previously-published S. cerevisiae data (SRX5086833, (DONOVAN et al 2019) ; SRX1176421, (MCKNIGHT et al 2016)), S. pombe data (SRX554384, (STEGLICH et al 2015) ; SRX331943, (DEGENNARO et al 2013)) and N. crassa data (SRX1596291, (SEYMOUR et al 2016) ;SRX2822417, (KLOCKO et al 2019)) were downloaded from the Sequence Read Archive (SRA) and analyzed using our computational pipeline to identify nucleosome dyad positions. Data were visualized using Integrated Genome Browser (FREESE et al 2016).…”
Section: Data Processingmentioning
confidence: 99%
“…Previous work show that WCC binding at the frq C-box region can be regulated by several chromatin modifiers that affect the nucleosome occupancy or positioning (Belden et al, 2011; Belden et al, 2007; Cha et al, 2013; Wang et al, 2014). We performed micrococcal nuclease digestion of Neurospora chromatin followed by deep sequencing (MNase-seq) as previously described (Seymour et al, 2016) to determine whether DNA replication affects nucleosome occupancy or positioning at the frq locus. MNase-seq data showed that although the nucleosome positioning at the frq locus in the WT strain was not affected by HU treatment, increased nucleosome occupancy was found at the frq promoter region, including the C-box, after HU treatment (Figure 4A), indicating that DNA replication affects nucleosome occupancy at the frq promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Micrococcal nuclease (MNase) experiments was performed as previously described (Seymour et al, 2016). Neurospora was cultured in petri dishes in liquid medium for two days.…”
Section: Star Methodsmentioning
confidence: 99%
“…In filamentous fungi, prominent classes of secondary metabolites are synthesized by large multimodular enzymes, the polyketide synthases (PKSs) and nonribosomal peptide synthetases (NRPSs) or hybrid NRPS-PKS/PKS-NRPS (Amnuaykanjanasin et al, 2009;Boettger et al, 2012). The genes encoding PKSs and NRPSs in filamentous fungi are often physically clustered with other functionally related genes (Bok et al, 2006) and tightly regulated through clusterspecific transcription factors (Netzker et al, 2015) or in some cases through the epigenetic regulators such as histone methyltransferases, histone deacetylases (Lee et al, 2009;Seymour et al, 2016). Among these, the epigenetic regulators such as histone methyltransferase 5 encoded by dim-5 in N. crassa are responsible for histone H3 lysine 9 trimethylation and play significant roles in heterochromatin formation (Lewis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%